Threadfin Porgy (Evynnis Cardinalis) Haplotype Pattern and Genetic Structure in Beibu Gulf, South China Sea - Xu, Lei; Wang, Xuehui; Wang, Lianggen; Ning, Jiajia; Li, Yafang; Huang, Delian; Liu, Shuangshuang; Du, Feiyan (Frontiers in Environmental Science, 2021)
Threadfin porgy (Evynnis cardinalis) is one of the important commercial fishing targets of bottom trawl fishery in the northern South China Sea. It is mainly threatened by overexploitation and listed as endangered species in the IUCN Red List. To investigate the demographic history and genetic structure of E. cardinalis population, partial sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene were obtained from 162 individuals collected from Beibu Gulf, South China Sea. In total, 44 different haplotypes were identified, and the dominant haplotype was found in all sampling sites. Across the dataset, nucleotide diversity was low, whereas haplotype diversity was high. Low pairwise comparisons of ΦST and high gene flow among sampling sites revealed a genetically homogeneous population structure in Beibu Gulf, indicating a single panmictic stock of E. cardinalis in this area. The star-like haplotype network, unimodal mismatch distribution, and significantly negative Tajima’s D and Fu’s Fs values indicated recent population demographic expansion of E. cardinalis. The mismatch distribution and Bayesian skyline plot results indicated that E. cardinalis from Beibu Gulf might have experienced colonization and demographic expansion due to sea level fluctuations during the late Pleistocene.